Implementing Teaching Writing Explanation Text using Mind Mapping and Popplet in Senior High School: A Classroom Action Research - Herlina, Santi Sri; Wigati, Asih Fikri; Kamil, Acep Bahrum (Journal of Educational Sciences, 2025)
The aim of this study is to investigate the implementation of mind mapping and Popplet techniques in the learning of the writing of explanatory texts. The research method involved a qualitative approach to classroom action research. Data were collected through observation, semi-structured interviews, and documentation. The research participants were twenty-three students from class XI MIPA at senior high school, with nine students selected as respondents through purposive sampling. The findings of this study indicate that the use of mind mapping and Popplet techniques helped students better comprehend the learning material. Students provided positive feedback on the application of mind mapping and the Popplet app, as they felt these tools assisted them in the process of writing explanatory texts. The use of mind mapping facilitated students' idea organization, while Popplet enabled the visualization and digital presentation of explanatory texts. The findings indicate that combining mind mapping and Popplet can enhance the efficiency and effectiveness of learning to write explanatory texts. This research offers teachers a new tool to employ innovative approaches to writing instruction, facilitating students' comprehension and proficiency.